2016
DOI: 10.1021/acs.est.5b04749
|View full text |Cite
|
Sign up to set email alerts
|

Ovatoxin-a, A Palytoxin Analogue Isolated from Ostreopsis cf. ovata Fukuyo: Cytotoxic Activity and ELISA Detection

Abstract: This study provides the first evaluation of the cytotoxic effects of the recently identified palytoxin (PLTX) analog, ovatoxin-a (OVTX-a), the major toxin produced by Ostreopsis cf. ovata in the Mediterranean Sea. Its increasing detection during Ostreopsis blooms and in seafood highlights the need to characterize its toxic effects and to set up appropriate detection methods. OVTX-a is about 100 fold less potent than PLTX in reducing HaCaT cells viability (EC50 = 1.1 × 10(-9) M vs 1.8 × 10(-11) M, MTT test) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 37 publications
4
19
3
Order By: Relevance
“…, Pelin et al. ). Several laboratory studies have shown that Ostreopsis exerts toxicity also on several marine organisms, both invertebrates and vertebrates (Faimali et al.…”
Section: Discussionmentioning
confidence: 99%
“…, Pelin et al. ). Several laboratory studies have shown that Ostreopsis exerts toxicity also on several marine organisms, both invertebrates and vertebrates (Faimali et al.…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity data of ovatoxins is limited, as only ovatoxin-a has been isolated in a sufficient amount for full structure elucidation (the other OVTXs are minor congeners) and it is possible that different analogues may present different toxin potencies [48]. Considering the biological activity, OVTX-a hemolytic effect was shown to be lower than that of the reference PLTX compound, and a study using HaCaT cells viability indicated that OVTX-a is about 100-fold less potent than PLTX, but it is more toxic than Ostreocin-d (another PLTX analogue) [49].…”
Section: Toxinsmentioning
confidence: 99%
“…Recent in vivo studies report a lower toxic potency of ostreocin-D by several administration routes, although LD 50 values are not provided [ 244 ]. Only in vitro studies are available for ovatoxin-a, which has shown 100-fold less toxic potency than PLTX in a skin keratinocyte cell line [ 255 ].…”
Section: Palytoxinmentioning
confidence: 99%